Réponses

2013-11-08T20:52:38+01:00
E = 4x² - 1 
=(2x+1)(2x-1)

F= (2x+1)(x+7) + (x-1)(x+7)
=(x+7)(2x+1+x-1)
=(x+7)3x

G= (2x + 1 )² - (3x-1)(2x + 1 )
=(2x+1)(2x+1)-(3x-1)(2x+1)
=(2x+1)(2x+1-3x+1)
=(2x+1)(-x+2)

H = 2x³ + 5x²
=x²(2x+5)

I = ( x-1)² - (2x-3)²
=(x-1-2x+3)(x-1+2x-3)
=(-x+2)(3x-4)

J= 4x² -12x +9
=(2x-3)²

K = (4x+3)(x-1) + 4x +3
=(4x+3)(x-1)+(4x+3)
=(4x+3)(x-1+1)
=(4x+3)x

L= 5 - x + (x-5)(2x+1)
=-(x-5)+(x-5)(2x+1)
=(x-5)(-1+2x+1)
=(x-5)2x
2013-11-08T21:02:49+01:00
Bonsoir
E = 4x² - 1 = (2x-1)(2x+1)
F = (2x+1)(x+7)+(x-1)(x+7) = (x+7)(2x+1+x-1) = (x+7)(3x)
G = (2x+1)² -(3x-1)(2x+1) = (2x+1)( 2x+1-3x+1) = (2x+1)(2-x) 
H = 2x^3+5x² = x²(2x+5)
I = (x-1)²-(2x-3)²= (x-1-2x+3)(x-1+2x-3) = (2-x)(3x-4)
J = 4x²-12x+9= (2x-3)²
K = (4x+3)(x-1) +4x+3 = 4x²+3x = x(4x+3)
L = 5-x+(x-5)(2x+1) = 2x²-10x = 2x(x-5)